Country Partnership Framework for the Federal Republic of Nigeria for the Period FY21-FY25 - World Bank (World Bank, Washington, DC, 2021)
To provide economic opportunities for its growing population, Nigeria needs to unlock private investment and job creation, and further the structural transformation and diversification of its economy. The low levels of human capital and the slow progress on diversification reflect and also contribute to the low levels and quality of public expenditures. The strategic objective of this Country Partnership Framework (CPF) is to support Nigeria to achieve progress on poverty reduction by promoting faster, more inclusive, and sustainable growth. Nigeria’s development agenda and development financing needs are vast, creating considerable excess demand for our support. Given Nigeria’s potential but also the critical challenges that it needs to address to realize that potential, the CPF proposes an ambitious engagement while recognizing the associated risks.